Tooth discoloration caused by nanographene oxide as an irrigant and intracanal medicament in the endodontic treatment of extracted single-rooted teeth: An ex-vivo study. - Abbas Abbaszadegan; Zeinab Rafiee; Bahar Asheghi; Ahmad Gholami (PLoS ONE)
Tooth discoloration caused by intracanal medicaments and irrigants presents a significant aesthetic challenge in dentistry. This study aimed to investigate the discoloration effects on tooth of nanographene oxide and positively charged silver nanoparticles and compares them with other commonly used materials in endodontic treatment. A total of 108 single-rooted, single-canal anterior mandibular and maxillary premolar teeth, extracted for orthodontic or periodontal reasons, were selected and prepared. The specimens were randomly divided into seven experimental groups and two control groups, each containing 12 samples. The experimental groups included three irrigants: nanographene oxide, sodium hypochlorite, and positively charged silver nanoparticles. The four medicament groups were nanographene oxide-carboxymethyl cellulose, positively charged silver nanoparticles-carboxymethyl cellulose, calcium hydroxide, and carboxymethyl cellulose. The control groups consisted of normal saline and blood. Discoloration was assessed at five time points: before material placement (T0), immediately after placement (T1), one week later (T2), one month later (T3), and three months later (T4). Spectrophotometric analysis was used to measure discoloration, and the ∆E values were statistically analyzed using repeated measures ANOVA and Tukey's post-hoc tests. After three months, no statistically significant difference in discoloration was observed among the irrigants (P > 0.05). However, the highest degree of discoloration was found in the silver nanoparticles group. Significant differences in ∆E values were noted between the normal saline group and both the silver nanoparticles (P = 0.001) and blood (P = 0.007) groups. Among the intracanal medicaments, a significant difference in ∆E values was observed between the carboxymethyl cellulose and calcium hydroxide groups (P = 0.005) at the final three-month examination. No significant differences were found among the other groups (P > 0.05). Nanographene oxide, used as both an irrigant and medicament, does not cause more discoloration than other commonly used materials in endodontic treatment. Therefore, it can be considered a viable alternative to traditional endodontic materials.